Pengaruh Konflik Kerja, Stres Kerja, Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Maju Hardware Madiun - Andita Puspitasari; Setyo Adjie; Siti Chamidah (ASSET: Jurnal Manajemen dan Bisnis, 2020)
This study aims to determine the effect of work conflict, work stress and work motivation on employee performance in advanced Hardware in Madiun. The hypothesis proposed in this study is; (1) It is suspected that Work Conflict has positive and significant effect on Employee Performance in Advanced Hardware Madiun, (2) Suspected Work Stress has a negative and significant effect on Employee Performance in Advanced Hardware Madiun, (3) Suspected Work Motivation has positive and significant effect on Employee Performance Advanced Hardware Madiun and (4) Allegedly Work Conflict, Job Stress, Work Motivation have positive and significant influence together on Employee Performance in Advanced Hardware Madiun. The population in this study were 64 employees at the Advanced Hardware Madiun Electronics Section. The sample used is Saturated Sampling means that all members of the population used as samples from this study were all employees of Advanced Hardware Madiun Electronics Section, totaling 64 employees. Data analysis method used is multiple linear regression with the help of SPSS. The results showed that; (1) Work Conflict has a positive effect (2,830) and significant effect on Employee Performance in Advanced Hardware Madiun, (2) Job Stress has a positive effect (2,513) and significant effect on Employee Performance in Advanced Hardware Madiun, (3) Work Motivation has a positive effect (2,152) and significant Employees at Advanced Hardware Madiun, and (4) Work Conflict, Job Stress, and Work Motivation have a positive effect of 5.164 and significant jointly on Employee Performance at Advanced Hardware Madiun.